Antibiotic Therapy: Sublethal Levels of Antibiotics Promote Bacterial Persistence in Epithelial Cells (Adv. Sci. 18/2020). Issue 18 (23rd September 2020) - Liu, Xiaoye; Liu, Fei; Ding, Shuangyang; Shen, Jianzhong; Zhu, Kui
Abstract : In article number 1900840, Jianzhong Shen, Kui Zhu, and co‐workers present how many extracellular bacteria can invade and survive in epithelial cells in both in vivo and in vitro models. Once such bacteria survive in host cells, they act as "Trojan horses" to tolerate various stresses including antibiotic therapy. Such adaption endows bacteria with common tolerance to multiple antibiotics. Sublethal levels of antibiotics not only promote the production of bacterial toxins to increase bacterial invasion, but also cause mitochondrial dysfunction and retard the clearance of internalized bacteria.